Promoting Sustainable Marketing in the RMG Sector: A Step for Transformation - Honey, Salma (AIUB Journal of Business and Economics, 2019)
Every day the business world is changing. Technological, environmental and social changes influence the business strategies dramatically. For this competitive world, manufacturers must concern regarding the changes of technological, environmental and social. So, the business organizations give their concentration in sustainable issues. Bangladeshi manufacturers are not away from these issues. The present study is an attempt to examine the overall understanding of the sustainable marketing practices in RMG sector in Bangladesh (BD). Readymade garments are the largest export earning sector in BD. The purpose of this study is to identify the present scenarios of sustainable marketing practices in BD and the importance of transformation in this regard. The findings of the study are based on both primary and secondary data. The primary data were collected from 20 garments industries from Dhaka and Gazipur districts. The samples were collected according to the convenience of the researcher. The data were analyzed using some qualitative tools of statistical data analysis. Finally, the study suggests some guidelines which will be beneficial to Bangladeshi manufacturers for adopting sustainable marketing practices and transformation strategies.